El marco jurídico de las operaciones de mantenimiento de la paz de Naciones Unidas - Iglesias Velasco, Alfonso J. (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2005)
The present article deals with the legal framework of peacekeeping operations that consists of international missions of military and/or police character deployed in the territory of one or more States —with their consent and cooperation— with the object of halting armed conflicts. After the system of collective security envisioned in the Charter of the United Nations was rendered obsolete by the Cold War, these operations were created by the UN as an alternative and, in fact, have become a mainstay in the worldwide organization’s efforts to maintain international peace and security. The Security Council is fundamentally, but not exclusively, responsible for peacekeeping according to article 24.1 of the Charter, and this implies that it is the only organ authorized to adopt coercive measures. In case the Security Council does not react to a specific warlike crisis —when, for instance, measures have been blocked by the veto of some of its permanent members— then the General Assembly retains a subsidiary role and can create peacekeeping operations, as these are then not considered coercive measures, but consensual. Also, this article explores the doctrinal controversy concerning the legal basis for these peace missions.